Disaster Risk Reduction Community Resilience and Responses - Zutshi, Bupinder; Ahmad, Akbaruddin; Srungarapati, Ananda Babu.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This book discusses the interconnected, complex and emerging risks in today's societies and deliberates on the various aspects of disaster risk reduction strategies especially through community resilience and responses. It consists of selected papers presented at the World Congress on Disaster Management, which focused on community resilience and responses towards disaster risk reduction based on South Asian experiences, and closely examines the coordinated research activities involving all stakeholders, especially the communities at risk. Further, it narrates the experiences of disaster risk-reduction in different communities that have policy implications for mitigation of future disaster risks in the societies affected by these types of disasters. Written from the social science perspective to disasters rather than an engineering approach, the book helps development and governance institutions to prioritize disasters as a problem of development rather than being parallel to it.
Chapter 1: The struggles of women: An Experience from the flood prone area -- Chapter 2: Innovative use of Technology (GIS) forStructural Inequality and Disaster Risk Reduction: An Indian Experience Disaster Risk Reduction- a case study -- Chapter 3: Bridging the Gap Between Academicians & Bureaucrats- the NYSAF Way -- Chapter 4: Recovery after Disasters- Problems and Prospects: The Case of Koslanda -Meeriyabedda Landslide in Sri Lanka -- Chapter 5: Indigenous Knowledge and Practices in Disaster Management: Experie -- Chapter 6: Nces of the Coastal People of Bangladesh -- Chapter 7: Mainstreaming Nuclear Disaster Risk Reduction in India -- Chapter 8: Integrating disaster management content in to social work curriculum-voices of social work students -- Chapter 9: Coordination Does Matter for Effective Disaster Management in the Coastal Areas in Bangladesh -- Chapter 10: Cyclone Aila: Immediate Challenges and Impact on Socio-Economy -- Chapter 11: Post-traumatic Stress Disorder and Depression among the Survivors of Nepal Earthquake: A Need Assessment Study -- Chapter 12: Linking Gender vulnerability and Disasters -- Chapter 13: A Sociological Perspective on 'Institutional Coordination' for Disaster Risk Reduction in India. <women and="" the="" gaps="" in="" framework="" of="" disaster="" risk="" reduction -- mapping="" vulnerable="" earthquake="" class="" i="" cities="" for="" reduction="" community="" resilience="" india -- law="" can="" set="" a="" stage="" reduction:="" study="" on="" nepal -- socio="" -="" economic="" impact="" coastal="" hazards="" fisher-folk="" livelihoods="" kerala -- sustainability="" managed="" projects -- post-disaster="" vulnerability="" female-headed="" households -- child="" centred="" (cc="" drr).
Keywords: Community development; Social service; Environmental sciences -- Social aspects; Natural disasters; Environmental management; Social Work and Community Development; Environmental Social Sciences; Natural Hazards; Environmental Management